Traditional Agricultural Practices Unique to Meemure Village, Kandy District Sri Lanka - Ananda, Tharaka; Nahallage, Charmalie (My University, 2016)
Meemure, located in the Central Province, in Kandy District, 343 km from Colombo is one of the unique villages in Sri Lanka that has about five hundred years of history and is remaining isolated from the main society with its own specific culture. Village prehistory has built on mythical stories related to “King Rawana” as well as folklores centered around a Vedda name “Beduruwa”; owner of the village during King Wimaladharmasuriya I (1542-1604). Due to its isolation from the main society many of the early traditions are still been preserved in this community. Therefore the main objective of this research is to study the traditional agricultural practices that are unique to them which they inherited from their forefathers. This is a descriptive study which used qualitative data collection methods. Questionnaire survey was conducted using seventy informants representing one person from each family and in depth interviews were conducted with five individuals. The study was conducted from April to November, 2013. Ninety percent of the Meemure villagers were farmers. Results revealed that the majority of the agricultural practices in Meemure village are unique to them. In paddy cultivation “Aluyanthraya adima”, traditional paddy storing system- “Vee atuwa” and many religious practices as well as land apportion system-“Pendi weta” (fence) and the methods used to construct the “Chena pala” in Chena cultivation cannot be seen in other cultures. However there is a gradual decrease in the usage of these practices nowadays thus it is necessary to record and protect these diminishing cultures.
Keywords: Diminishing cultures; Folk lore; Religious practices; Chena cultivation